Ferric citrate in the management of hyperphosphataemia and iron deficiency anaemia: A meta-analysis in patients with chronic kidney disease - Choi, Yeo Jin; Noh, Yoojin; Shin, Sooyoung (British Journal of Clinical Pharmacology, 2021)
Aims: Phosphate-lowering effects of ferric citrate were reported in several clinical trials, but mostly in small-scale studies. The aim of this meta-analysis was to investigate the efficacy and safety of ferric citrate in controlling hyperphosphataemia and iron-deficiency anaemia in chronic kidney disease (CKD) patients. Methods: PubMed, Embase and Cochrane Library were searched for clinical trials that enrolled CKD patients receiving ferric citrate for hyperphosphataemia. Two investigators performed systematic literature search to identify eligible studies, evaluated risk of bias and extracted relevant data. Results: Sixteen studies were included in the meta-analysis. Phosphate-lowering effects of ferric citrate were greater compared to no active treatment (standardized mean difference [SMD] = −1.15; P < 0.001) and comparable to other phosphate binders (SMD = 0.03; P = 0.61). Calcium concentrations post ferric citrate treatment did not differ compared to no active treatment (SMD = 0.15; P = 0.21) but were significantly lower compared to other phosphate binders (SMD = −0.14; P = 0.01). These led to significant reductions in calcium-phosphorus product with ferric citrate versus no active control (SMD = −1.02; P < 0.001) but no difference versus active control (SMD = −0.01; P = 0.93). Intact parathyroid hormone showed no substantial between-group difference in both comparison against no active and active controls. Ferric citrate improved iron stores and anaemia parameters, but increased risk of diarrhoea, abdominal pain and discoloured faeces. Conclusion: Ferric citrate was effective in lowering phosphorus and phosphorus-calcium product versus no active treatment and had comparable effects versus other phosphate binders. Calcium levels were significantly lower with ferric citrate than with other phosphate-lowering treatment. Ferric citrate had additive effects on iron repletion and anaemia control and was associated with mostly gastrointestinal side effects.
Keywords: Anemia, Iron-Deficiency; Ferric Compounds; Humans; Hyperphosphatemia; Phosphates; Renal Insufficiency, Chronic; chronic kidney disease; ferric citrate; hyperphosphataemia; phosphate binder